2006
DOI: 10.2478/s11756-006-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Water temperatures and ice cover in lakes of the Tatra Mountains

Abstract: In 2000 and 2001, miniature thermistors with integrated data loggers were employed to measure lake surface water temperatures (LSWTs) and temperature profiles in high-altitude mountain lakes lying between 1580 and 2145 m a.s.l. on both the Slovak and Polish sides of the Tatra Mountains. This allowed the annual cycle of water temperatures and ice cover in these lakes to be described quantitatively, and their dependence on lake altitude above sea level to be investigated. LSWTs in the Tatra Mountains are found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 13 publications
3
27
1
Order By: Relevance
“…The approximately linear decrease in littoral water surface temperature with increasing altitude has been shown in various mountain ranges (e.g. Lotter et al, 1997;Sˇporka et al, 2006). In our study, some parameters of the chironomid assemblages showed clear trends with altitude.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The approximately linear decrease in littoral water surface temperature with increasing altitude has been shown in various mountain ranges (e.g. Lotter et al, 1997;Sˇporka et al, 2006). In our study, some parameters of the chironomid assemblages showed clear trends with altitude.…”
Section: Discussionsupporting
confidence: 61%
“…Lake thermal cycles depend on several local factors such as lake orientation, landscape morphometry, mean lake depth and lake surface to volume ratio (Brodersen and Anderson, 2000). Sˇporka et al (2006) demonstrated a high degree of variability in the timing of the ice-cover period in Tatra lakes as a consequence of individual lake morphometry, lake setting, and rate of inflow. The importance of lake setting was also emphasised by Łajczak (1982), who showed ice cover duration to be dependent on whether the lake faces north or south.…”
Section: Discussionmentioning
confidence: 99%
“…The list of the examined lakes and their basic parameters is given in Table 1. Detailed morphometry, hydrography hydrology and the thermal regime of the observed lakes was published by GREGOR &PACL (2005) andŠPORKA et al (2006). Investigated outlets and especially inlets were not uniform.…”
Section: Study Areamentioning
confidence: 99%
“…Because of windy weather during the sampling and low temperatures (1 to 10 • C; median of 5 • C), the lakes were likely mixed to depths greater than the epilimnion. For details on seasonal trends in temperature of the Tatra lakes see ŠPORKA et al (2006).…”
Section: Sampling and Analysesmentioning
confidence: 99%